Sleep duration in middle-aged years of life predicts the age of diagnosis of Parkinson's disease - Cayla E. Clark; Joshua Gold; B. Rhett Rigby (Sleep Medicine: X)
Introduction: Chronic short sleep duration (i.e., <7 h sleep daily) could reduce the brain's ability to attenuate toxin and protein accumulation, which may contribute to Parkinson's disease (PD). The purpose of this study was to characterize the relationship between self-reported sleep duration from adolescence to adulthood and the age of diagnosis in people with PD. A secondary purpose was to characterize the interaction between sleep duration and physical activity through the lifespan on the age of PD diagnosis. Methods: A secondary data analysis was performed using the Fox Insight data set. Multiple regression analysis was used to determine the age range that sleep duration best predicted the age of diagnosis of PD. Hierarchical linear multiple regression was performed to assess if self-reported sleep duration, physical activity, and their interaction predicted the age of diagnosis for PD, after accounting for sociodemographic factors. Results: Both sleep (p < 0.001) and physical activity time (p = 0.013) significantly predicted the of age of onset of PD. In contrast, there was no evidence to support an interaction of sleep by physical activity on the age of diagnosis of PD. Sleep duration at 46–55 years maintained significance after controlling for education, income, race, ethnicity, and sex (p < 0.001). Weekly duration of time spent performing moderate-intensity physical activity was added as an input variable. Conclusion: Sleep duration significantly predicts the age of diagnosis of PD, with shorter sleep duration associated with a younger age of diagnosis of PD.